Critical evaluation of accident tolerant fuel selection criteria for APR-1400 nuclear reactors - Mohammad Alrwashdeh; Asma Alzarooni; Khurrum Saleem Chaudri; Maithah Alaleeli; K. Karuppasamy; Andreas Schiffer; Imran Afgan; Daniel Choi; Saeed A. Alameri (Advances in Physics: X)
The United Arab Emirates (UAE) launched its nuclear energy program in 2008, achieving notable outcomes with the ‘UAE Policy on the Peaceful Use of Nuclear Energy’ program. This initiative is dedicated to ensuring the operational safety, reliability, and efficient operation of its advanced nuclear reactor (APR-1400) power plants. In the aftermath of the Fukushima incident, the global nuclear fuel research and development community shifted toward developing accident-tolerant fuels (ATFs). ATFs are purposefully engineered and manufactured to withstand delayed periods of core cooling system disruption, thereby significantly enhancing safety compared to conventional fuel systems while maintaining or improving normal operational performance. This research investigates the feasibility of implementing ATFs as the primary nuclear fuel source within APR-1400 nuclear reactor and evaluates their potential effect on the operational parameters and safety. In order to accomplish this objective, comprehensive review and assessments of the potential ATFs, including neutronics, thermal-hydraulic, thermomechanical/chemical, and fuel performance evaluations, were conducted, encompassing multiple candidate ATF concepts. This research aims to overview ongoingresearch efforts and prospective ATF concepts for near-future implementation within APR-1400 nuclear power plants.